2011
DOI: 10.1111/j.1528-1167.2010.02885.x
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of the relation between vaccination and occurrence of seizures in Dravet syndrome

Abstract: Summary Dravet syndrome is a severe epileptic encephalopathy starting in the first year of life. Mutations in SCN1A can be identified in the majority of patients, and epileptic seizures in the setting of fever are a clinical hallmark. Fever is also commonly seen after vaccinations and provocation of epileptic seizures by vaccinations in patients with Dravet syndrome has been reported, but not systematically assessed. In a retrospective evaluation of 70 patients with Dravet syndrome and SCN1A mutations, seizure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 14 publications
5
51
0
Order By: Relevance
“…This is in line with a reported onset of seizures after age 2 months in most cases of DS, 6,13 probably resulting from age-dependent SCN1A expression. 24 Table 4 Risk of vaccination-associated seizures after seizure onset for (pertussis) combination vaccines in the first 2 years of life in Dravet syndrome Several cohort studies have described subsequent seizures following pertussis combination vaccines, 10,13,21 and our study provides novel data on the quantitative risk of vaccination-associated seizures after seizure onset in DS. Our study shows that replacement of wP by aP combination vaccines leads to fewer vaccination-associated seizures in DS.…”
Section: Risk Of Seizures After Mmr Vaccinations In Dsmentioning
confidence: 88%
See 2 more Smart Citations
“…This is in line with a reported onset of seizures after age 2 months in most cases of DS, 6,13 probably resulting from age-dependent SCN1A expression. 24 Table 4 Risk of vaccination-associated seizures after seizure onset for (pertussis) combination vaccines in the first 2 years of life in Dravet syndrome Several cohort studies have described subsequent seizures following pertussis combination vaccines, 10,13,21 and our study provides novel data on the quantitative risk of vaccination-associated seizures after seizure onset in DS. Our study shows that replacement of wP by aP combination vaccines leads to fewer vaccination-associated seizures in DS.…”
Section: Risk Of Seizures After Mmr Vaccinations In Dsmentioning
confidence: 88%
“…9 Our finding of lower risks following aP vaccines is in agreement with the reduced risk of febrile seizures in the general pediatric population, 25,26 even though vaccination-associated seizures in DS frequently occurred without fever in our and previous studies. 9,10,14,21 These reductions in seizure risk are probably explained by lower reactogenicity of aP vs wP vaccines. 15 Seizures in the risk period following MMR vaccinations have only occasionally been reported in DS 10,21,27 but were very common in our cohort.…”
Section: Risk Of Seizures After Mmr Vaccinations In Dsmentioning
confidence: 95%
See 1 more Smart Citation
“…The ages ranged from of 3 months to 4.5 years, relatively younger than our patient. They reported that status epilepticus occurred in 8 patients among those who manifested seizure, without mentioning the neurological outcome [9] . In our case, the fl u vaccination may have triggered the acute encephalopathy.…”
Section: Discussion ▼mentioning
confidence: 99%
“…Seizure precipitation by vaccination or fever is a hallmark of SCN1A-related Dravet syndrome. 15,[30][31][32] Although fever is a known seizure precipitant in children with a PCDH19 mutation, a 1q-terminal deletion, and SCN1A-related GEFS+ syndrome, [33][34][35][36] our study is the first to acknowledge vaccination-related onset in the latter 3 syndromes. A chance association is unlikely because vaccinationrelated seizures recurred after a second vaccination in both the GEFS+ and 1qter case, occurred in an additional case of SCN1A-related GEFS+ syndrome with only febrile seizures (Table 1), and have previously been reported in another girl with a PCDH19 mutation 19 and 2 GEFS+ cases.…”
Section: Figurementioning
confidence: 99%